ENGINEERING CURRICULUM DESIGN USING QUALITY FUNCTION DEPLOYEMENT - Okay Işık; Yunus Emre Seğmen; Mehmet Kölemen (Havacılık ve Uzay Teknolojileri Dergisi, 2012)
In this study, a Quality Function Deployment framework proposed in the design of engineering curriculum. The proposed model is applied to the curriculum of Industrial Engineering Department of Turkish Air Force Academy (TuAFA)in an effort to see the pros and cons. Considering its role as the main source of officers employed in the Turkish Air Force, TuAFA’s engineering programs should be designed to match the needs of a specific customer and should be more mission oriented. It has been assumed that these expectations are cadets’ qualifications or program goals and we applied Analytical Hierarchy Process to prioritize these expectations. The direct and indirect contributions of courses to program goals are also considered. QFD framework proved to be well suited to vocational education needs of TuAFA.